Bkaʼ rdzogs pa chen po yaṅ zab dkon mchog spyi ʼdus las rtsa ba gsum gyi las byaṅ - ʼJaʼ-tshon-sñiṅ-po, Gter-ston, 1585-1656 (s.n., 1974)
Ritual for the propitiation of the rtsa gsum, i.e. the guru, dakinis, and protective deities, from the Dkon mchog spyi 'dus cycle of rediscovered teachings.